Bacteria autoaggregation: how and why bacteria stick together - Nwoko, El-Shama Q A; Okeke, Iruka N (Biochemical Society transactions, 2021)
Autoaggregation, adherence between identical bacterial cells, is important for colonization, kin and kind recognition, and survival of bacteria. It is directly mediated by specific interactions between proteins or organelles on the surfaces of interacting cells or indirectly by the presence of secreted macromolecules such as eDNA and exopolysaccharides. Some autoaggregation effectors are self-associating and present interesting paradigms for protein interaction. Autoaggregation can be beneficial or deleterious at specific times and niches. It is, therefore, typically regulated through transcriptional or post-transcriptional mechanisms or epigenetically by phase variation. Autoaggregation can contribute to bacterial adherence, biofilm formation or other higher-level functions. However, autoaggregation is only required for these phenotypes in some bacteria. Thus, autoaggregation should be detected, studied and measured independently using both qualitative and quantitative in vitro and ex vivo methods. If better understood, autoaggregation holds the potential for the discovery of new therapeutic targets that could be cost-effectively exploited.